The effects of interactive reading on young children’s narrative abilities: a meta-analytic study - Xing, Lei; Tang, Yi; Liu, Qingke; Chen, Haifeng; Zeng, Jiamin; Su, Junyue (Frontiers in Psychology, 2025)
BackgroundThe development of narrative abilities during early childhood forms the foundation for more complex language expression and comprehension later in life. This study employs a meta-analytic approach to systematically evaluate and infer the effects of interactive reading on young children’s narrative abilities.MethodsInclusion criteria for eligible studies were established. Electronic databases, including CNKI, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis, Wiley, and ERIC, were systematically searched for experimental or quasi-experimental studies investigating the effects of interactive reading on young children’s narrative abilities. A moderator analysis was subsequently conducted to explore potential factors influencing the effectiveness of interactive reading interventions.ResultsA total of 25 studies (k = 123 independent effect sizes; N = 2,886 participants) were included. Random-effects modeling revealed significant heterogeneity (I2 = 76.07%, p < 0.001). Key findings: (1) Interactive reading exerted a medium aggregate effect on narrative ability development [g = 0.425, 95% CI (0.333, 0.518), p < 0.001], per Cohen’s benchmarks. (2) The effect on children’s narrative development was significantly moderated by the duration of the interactive reading intervention. (3) Incorporating peer sharing during interactive reading significantly enhanced the development of children’s narrative abilities.ConclusionInteractive reading has a positive intervention effect on children’s narrative abilities, and this effect is influenced by multiple moderating variables. This meta-analysis provides quantitative evidence supporting the role of interactive reading in promoting the development of children’s narrative abilities. Future meta-analyses could simultaneously include both preschool and school-age children to compare and analyze the intervention effects across different age groups.Systematic review registrationdoi: 10.37766/inplasy2025.10.0086, INPLASY2025100086.